ANALISIS STRATEGI KORPORASI TOYOTA DALAM MENDUKUNG KEMAJUAN PEREKONOMIAN NEGARA - Musyfiq Amrullah, Musyfiq Amrullah; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Muhajirin, Muhajirin; Abdussalam, Abdussalam; Budiman Fauzi, Budiman Fauzi; Dewi Arita, Dewi Arita (Media Nusantara, 2023)
The Corporate Strategy course is one of the mandatory courses in the Economics Study Program at the Nahdlatul Ulama College of Islamic Economics and Industrial Engineering, Faculty of Engineering, Islamic University of the Archipelago. Corporate Strategy is a strategy related to choosing the direction of the company as a whole, as well as managing the business and product portfolio. This strategy is the company's overall orientation towards growth, stability or rethenchment.The goal of Toyota's corporate strategy analysis is to help companies understand their position in the market and develop effective long-term strategies to achieve their business goals. Some specific objectives of Toyota corporate strategy analysis may include:Understanding the External Environment: Identify external factors such as economic, political, technological, social and environmental that can influence Toyota's business. This helps in capturing opportunities and anticipating threats in the global market. Analyzing the Internal Environment: Evaluate Toyota's internal resources such as operational strengths, technological capabilities, competitive advantages, and organizational culture. This helps identify strengths that can be optimized and weaknesses that need to be addressed. Developing Vision and Mission, Identifying Corporate Strategy, Optimizing Organizational Structure, Measuring Performance and Managing Risk. Overall, the goal of Toyota's corporate strategy analysis is to increase the company's long-term competitiveness and profitability, while considering the external and internal factors that influence their performance in the global automotive market.